Scale-up and large-scale production of Tetraselmis sp CTP4 (Chlorophyta) for CO2 mitigation: from an agar plate to 100-m(3) industrial photobioreactors - Pereira, Hugo (2018)
ABSTRACT: Industrial production of novel microalgal isolates is key to improving the current portfolio of available strains that are able to grow in large-scale production systems for different biotechnological applications, including carbon mitigation. In this context, Tetraselmis sp. CTP4 was successfully scaled up from an agar plate to 35-and 100-m(3) industrial scale tubular photobioreactors (PBR). Growth was performed semi-continuously for 60 days in the autumn-winter season (17th October -14th December). Optimisation of tubular PBR operations showed that improved productivities were obtained at a culture velocity of 0.65-1.35 m s(-1) and a pH set-point for CO2 injection of 8.0. Highest volumetric (0.08 +/- 0.01 g L-1 d(-1)) and areal (20.3 +/- 3.2 g m(-2) d(-1)) biomass productivities were attained in the 100-m(3) PBR compared to those of the 35-m(3) PBR (0.05 +/- 0.02 g L-1 d(-1) and 13.5 +/- 4.3 g m(-2) d(-1), respectively). Lipid contents were similar in both PBRs (9-10% of ash free dry weight). CO2 sequestration was followed in the 100-m(3) PBR, revealing a mean CO2 mitigation efficiency of 65% and a biomass to carbon ratio of 1.80. Tetraselmis sp. CTP4 is thus a robust candidate for industrial-scale production with promising biomass productivities and photosynthetic efficiencies up to 3.5% of total solar irradiance.